Transnationalism and the Politics of "Home" for Philippine Domestic Workers - Barber, Pauline Gardiner (Anthropologica, 2022)
Gendered labour migration and transnationalism have become part of the ideological fabric of Filipino culture and nationhood. Local livelihoods and the meanings of "home" are being socially, politically and spatially recast through the unprecedented scale of women’s migration. This article explores the cultural politics of Philippine labour migration and offers a critique of victimizing representations of Filipina. Homogenizing cultural idioms portray Filipina as dutiful daughters in families and of the nation, yet migrants’ narratives reveal their agency and indicate their differences. Questions are also raised about whether the idea of a travelling culture accommodates the contradictory experiences of migrants. From their perspective, political aspects of travel, culture and economy are elided through a discourse of travelling, flux and the fetishization of the in-between mode.